PERILAKU SOSIAL PADA ANAK YANG KECANDUAN BERMAIN GADGET SELAMA MASA PANDEMI COVID 19 DI KARANGANYAR (Lembaga Pengembangan Kinerja Dosen, 2023)
Gadgets are a form of electronic media that is widely used among the general public, especially children who are still in school. The use of gadgets is very influential on children's social behavior, especially in the way they interact with their social or environment, even though children's gadgets become more emotional and forget time, often neglecting their obligations as students. From that problem, this study aims to determine the social behavior of children who are addicted to playing gadgets during the current pandemic. This study used qualitative research methods. Data collection techniques using observation, structured and in-depth interviews. The research subjects consisted of 10 subjects: 7 children aged 9–13 years, 2 housewives, and 1 mother who worked as a teacher. The results showed that gadgets can affect social behavior in children. The importance of the role of parents during online learning at home is to always be able to provide supervision and knowledge about the use of gadgets that should be useful and not have a negative impact on children.